2020
DOI: 10.1002/biot.202000117
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots: A Review from Concept to Clinic

Abstract: Quantum dots (QDs) are semiconductor materials that have gained great interest due to their unique characteristics like optical properties. They are extensively being used in different areas, including solar cells, light-emitting diodes, laser technology, as well as biological and biomedical applications. In this review, comprehensive information about different aspects of QDs is provided, including their types and classifications, synthesis approaches, in vitro and in vivo toxicity, biological applications, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 249 publications
(278 reference statements)
0
101
0
1
Order By: Relevance
“…provide a review on the role of quantum dots, with a focus on in vitro and in vivo studies, as well as a discussion about the clinical translation of these structures. [ 2 ] Increasing the focus on the therapeutic potential of nanomaterials, the requests for the development of biocompatible devices for tissue regeneration or replacement are investigated by Raut et al. [ 3 ] Discussion on tissue regeneration continues with a review by Abdollahiyan et al.…”
mentioning
confidence: 99%
“…provide a review on the role of quantum dots, with a focus on in vitro and in vivo studies, as well as a discussion about the clinical translation of these structures. [ 2 ] Increasing the focus on the therapeutic potential of nanomaterials, the requests for the development of biocompatible devices for tissue regeneration or replacement are investigated by Raut et al. [ 3 ] Discussion on tissue regeneration continues with a review by Abdollahiyan et al.…”
mentioning
confidence: 99%
“…The QDs without polymer protection shows the release of toxic cadmium on exposure to ultraviolet radiation [158][159][160][161]. In vitro toxicity studies of CdSe QDs on primary hepatocytes showed acute toxicity profile due to the liberation of free Cd2+ ions [162][163][164]. SPIONs are thought to be less toxic under in vivo conditions as they are considered to be biodegradable [165,166].…”
Section: Toxicity Apprehensionmentioning
confidence: 99%
“…The diameter of QDs is usually within 1–10 nm. [ 23 ] Because of their ultrathin emission spectrum and resistance to photobleaching, QDs are widely used in many fields and applications, such as in light‐emitting diodes, biosensing, bioimaging, and diagnostics. [ 23,24 ] However, adverse effects may occur to workers in QD production‐related industries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Because of their ultrathin emission spectrum and resistance to photobleaching, QDs are widely used in many fields and applications, such as in light‐emitting diodes, biosensing, bioimaging, and diagnostics. [ 23,24 ] However, adverse effects may occur to workers in QD production‐related industries. [ 25 ] Respiratory inhalation is one of the main routes of exposure to QDs during the production, processing, transportation, and usages in an occupational environment.…”
Section: Introductionmentioning
confidence: 99%